1996
DOI: 10.1111/j.1471-6712.1996.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technologies in Stroke Rehabilitation from a User Perspective

Abstract: The purpose of the study was to provide knowledge, from a user perspective, about the selection process for assistive devices. Thirty-eight persons who had suffered stroke were interviewed about their assistive devices, approximately one year after stroke. It was found that the patients had little influence on the choice of assistive devices and that the maintenance and follow-up routines varied among patients. In some cases follow-up was not done at all. Despite these deficits, the patients used their assisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…More than half of those living in their own houses or apartments had had adjustments made to their homes on discharge from the rehabilitation ward, which is in accordance with earlier studies of stroke victims [7, 8]. In this study, both home adaptation and assistive devices were aimed at facilitating ADL activities and mobility indoors and outdoors, which agrees with two other Swedish studies of elderly people [20, 21]and studies of stroke victims and elderly people [7, 20, 22]. When comparing the use of different kinds of mobility devices in the various accommodations it was found that walking sticks and crutches were more frequently used by people living in the community than by those living in institutions.…”
Section: Discussionsupporting
confidence: 80%
“…More than half of those living in their own houses or apartments had had adjustments made to their homes on discharge from the rehabilitation ward, which is in accordance with earlier studies of stroke victims [7, 8]. In this study, both home adaptation and assistive devices were aimed at facilitating ADL activities and mobility indoors and outdoors, which agrees with two other Swedish studies of elderly people [20, 21]and studies of stroke victims and elderly people [7, 20, 22]. When comparing the use of different kinds of mobility devices in the various accommodations it was found that walking sticks and crutches were more frequently used by people living in the community than by those living in institutions.…”
Section: Discussionsupporting
confidence: 80%
“…Previous research found that although follow-up is lacking, clients may use ATDs as intended (19). The results from this study confirm that some clients learned to use their ATDs and thus overcame their occupational performance difficulties with minimal assistance from the occupational therapist.…”
Section: Discussionsupporting
confidence: 75%
“…To facilitate client-centred ATD service delivery, the occupational therapist should work in a close and collaborative relationship with the client during all stages of the service delivery process (16)(17)(18). However, clients report that the follow-up for prescribed ATD varies or is lacking (19,20). In one survey, 69% of clients reported that they did not receive any follow-up on the ATD after it had been prescribed (20).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the rollator proves to be a useful device for people with restricted walking ability suggesting that this societal intervention is worthwhile. Furthermore, AT is not costly compared to other rehabilitation interventions 23 indicating that rollators probably are cost-effective. Nearly all users were satisfied with other people's reactions and support, mirroring the fact that rollators have become 'normalized' and that it is not so stigmatising to use one anymore.…”
Section: Discussionmentioning
confidence: 97%